1977
DOI: 10.1068/p060113
|View full text |Cite
|
Sign up to set email alerts
|

Vision with Isoluminant Colour Contrast: 1. A Projection Technique and Observations

Abstract: An optical technique is described for projecting two-colour pictures with controlled brightness contrast, which may be set to zero-at isoluminance. Colour registration is maintained without adjustment or special setting up. It is suggested that colour-and brightness-contour registration in the visual channel is a problem which may be solved neurally be master brightness signals locking slave colour signals. The projection apparatus allows the supposed master brightness signals to be removed-at isoluminance-whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
94
4
3

Year Published

1979
1979
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(112 citation statements)
references
References 4 publications
11
94
4
3
Order By: Relevance
“…(1) Von der Heydt, Peterhans, and Baumgartner (1984) have recently shown that certain cells in V2 (area 18) of the monkey respond quite strongly to illusory contours, and (2) illusory contours cannot be produced in the absence of luminance contrast between the disks and background texture. For example, if isoluminant color contours (Gregory, 1977), cyclopean targets (Prazdny, 1985), or texture boundaries (Cavanagh, personal communication, 1985) are used to define the cut sectors, then no illusory contours are seen. Also, as noted (a) (b) those in the interstripes are sensitive primarily to bar length ("form").…”
Section: •••••••mentioning
confidence: 99%
“…(1) Von der Heydt, Peterhans, and Baumgartner (1984) have recently shown that certain cells in V2 (area 18) of the monkey respond quite strongly to illusory contours, and (2) illusory contours cannot be produced in the absence of luminance contrast between the disks and background texture. For example, if isoluminant color contours (Gregory, 1977), cyclopean targets (Prazdny, 1985), or texture boundaries (Cavanagh, personal communication, 1985) are used to define the cut sectors, then no illusory contours are seen. Also, as noted (a) (b) those in the interstripes are sensitive primarily to bar length ("form").…”
Section: •••••••mentioning
confidence: 99%
“…There is some evidence that illusory contours of the Schumman/Kanisza type are associated with the brightness-domain processing. For example, inducing forms defined solely by hue (i.e., the forms and the surrounding areas are isoluminant) seem to produce, at most, only weak subjective contours (Frisby & Clatworthy, 1975;Gregory, 1977). In the first experiment, we investigated whether illusory contours could be brought about by inducers defined in other domains (spatial and temporal correlation, and flicker) in the absence of monocular luminance-domain cues.…”
mentioning
confidence: 99%
“…In this case, we expected that the strength of the · subjective contour would be reduced or that it would not be seen at all. Luminance contrast is known to be critical for the formation of static subjective contours (Frisby and Clatworthy 1975;Gregory 1977), the perception of apparent motion (Ramachandran and Gregory 1978;Cavanagh et al 1985), and the perception of achromatic neon spreading (Bressan 1993 2.2.2 Procedure. Ten stimuli, varying in luminance and chromaticity of the test and surround dots as described above, were presented in random order.…”
mentioning
confidence: 99%